リハビリテーション病院退院者のスポーツ活動の実施状況 : 主に茨城県居住者を対象とした調査 - 内田, 智子; 浅川, 育世; 橋爪, 佑子; 水上, 昌文; 松田, 智行; 齋藤, 由香; 大仲, 功一; 伊佐地, 隆; 橘, 香織 (障害者スポーツ科学, 2013)
To develop appropriate sports programs for people with disabilities, it is important to elucidate their obstacles and needs with respect to sports activity. This study clarified the factors that affected people's participation in sports activity and the kinds of sports activities they were interested in. Seventy-nine adults who had been discharged from a rehabilitation hospital in south Ibaraki 3 months earlier completed self-administered questionnaires assessing their interests in sports participation, actual sports activity, and the activities they wanted to participate in. Just 23 (37%) actually participated in any sports activity. In the nonparticipant group, preference for sports activity (adjusted OR=9.58, CI 2.97-30.96) and the care needs level (adjusted OR=5.59, CI 1.14-27.5) were significantly related to their sports activity behavior. The reasons why individuals did not participate in any sports activity included worries about health, absence of interest in sports activity, problems with accessibility, and lack of information about what kind of sports program they could join. The most popular activity was "walking," although some showed interest in outdoor team sports such as soccer or baseball. The effect sizes were modest but suggest that people with disability in Ibaraki want safe, enjoyable sports programs.